B chromosome dynamics in Prochilodus costatus (Teleostei, Characiformes) and comparisons with supernumerary chromosome system in other Prochilodus species - Melo, Silvana [UNESP]; Utsunomia, Ricardo [UNESP]; Penitente, Manolo [UNESP]; Sobrinho-Scudeler, Patricia Elda [UNESP]; Porto-Foresti, Fabio [UNESP]; Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP]; Dergam, Jorge Abdala (Pensoft Publ, 2017)
Within the genus Prochilodus Agassiz, 1829, five species are known to carry B chromosomes, i.e. chromosomes beyond the usual diploid number that have been traditionally considered as accessory for the genome. Chromosome microdissection and mapping of repetitive DNA sequences are effective tools to assess the DNA content and allow a better understanding about the origin and composition of these elements in an array of species. In this study, a novel characterization of B chromosomes in Prochilodus costatus Valenciennes, 1850 (2n=54) was reported for the first time and their sequence complementarity with the supernumerary chromosomes observed in Prochilodus lineatus (Valenciennes, 1836) and Prochilodus argenteus Agassiz, 1829 was investigated. The hybridization patterns obtained with chromosome painting using the micro B probe of P. costatus and the satDNA SATH1 mapping made it possible to assume homology of sequences between the B chromosomes of these congeneric species. Our results suggest that the origin of B chromosomes in the genus Prochilodus is a phylogenetically old event.
Keywords: additional chromosomes; genome; Prochilodontidae